Maternal Pre-conception Body Mass Index and Fasting Plasma Glucose With the Risk of Pre-term Birth: A Cohort Study Including 4.9 Million Chinese Women - Xu, Qin; Zhou, Qiongjie; Yang, Ying; Liu, Fangchao; Wang, Long; Wang, Qiaomei; Shen, Haiping; Xu, Zongyu; Zhang, Yiping; Yan, Donghai; Peng, Zuoqi; He, Yuan; et al. (Frontiers in Reproductive Health, 2021)
Background To evaluate the associations of preconception body mass index (BMI), fasting plasma glucose (FPG) alone and their combination with preterm birth (PTB) risk. Methods We conducted a population-based retrospective cohort study with 4987129 reproductive-aged women, who participated in National Free Pre-Pregnancy Checkups Project in 2013-2016 and had a singleton delivery before Dec 2017 in China. All data analyses were conducted in 2018‒2021. Results A total of 339,662 (6.81%) women had preterm deliveries. Compared with women with normal weight and normal glucose, underweight and normal weight were associated with PTB among hypoglycemia women, the adjusted odd ratios (aORs) were 1.24 (95% CI: 1.05-1.48) and 1.16 (95% CI: 1.07-1.25), respectively; underweight, overweight and obesity were associated with PTB among women with normal glucose, the aORs were 1.09 (95% CI: 1.08-1.10), 1.06 (95% CI: 1.05-1.07) and 1.08 (95% CI: 1.05-1.12), respectively; all the BMI groups were significantly associated with PTB among women with prediabetes or diabetes (P<0.05). The dose-response relationships of BMI with PTB varied in different FPG level, with U-shaped curve in normal glucose and prediabetes women, J-shaped in diabetes women, L-shaped in hypoglycemia women. For FPG with PTB, the dose-response relationships were U-shaped in normal weight, overweight, and obesity women, and L-shaped in underweight women. Conclusion We found that the associations of PTB with BMI varied with levels of FPG, and associations of PTB with FPG varied with levels of BMI. There was a synergistic effect on PTB risk due to abnormal weight and glycemia besides a conventional main effect derived from either of them. Achieving desirable weight and glucose control before conception should be advised.